INPP5D regulates inflammasome activation in human microglia - Vicky Chou; Richard V. Pearse; Aimee J. Aylward; Nancy Ashour; Mariko Taga; Gizem Terzioglu; Masashi Fujita; Seeley B. Fancher; Alina Sigalov; Courtney R. Benoit; Hyo Lee; Matti Lam; et al. (Nature Communications, 2023)
Abstract Microglia and neuroinflammation play an important role in the development and progression of Alzheimer’s disease (AD). Inositol polyphosphate-5-phosphatase D (INPP5D/SHIP1) is a myeloid-expressed gene genetically-associated with AD. Through unbiased analyses of RNA and protein profiles in INPP5D-disrupted iPSC-derived human microglia, we find that reduction in INPP5D activity is associated with molecular profiles consistent with disrupted autophagy and inflammasome activation. These findings are validated through targeted pharmacological experiments which demonstrate that reduced INPP5D activity induces the formation of the NLRP3 inflammasome, cleavage of CASP1, and secretion of IL-1β and IL-18. Further, in-depth analyses of human brain tissue across hundreds of individuals using a multi-analytic approach provides evidence that a reduction in function of INPP5D in microglia results in inflammasome activation in AD. These findings provide insights into the molecular mechanisms underlying microglia-mediated processes in AD and highlight the inflammasome as a potential therapeutic target for modulating INPP5D-mediated vulnerability to AD.